Architecting systems‐of‐systems and their constituents: A case study applying Industry 4.0 in the construction domain. Issue 6 (24th October 2019) - Axelsson, Jakob; Fröberg, Joakim; Eriksson, Peter
Abstract: The development of system‐of‐systems (SoS) requires a continuous interplay between design decisions on the SoS level and those on the level of its constituent systems (CS), which often preexist and need to be adapted as the SoS evolves. This involves not only preparing the CS to participate in a particular SoS, but also designing the CS architecture to make it easily adaptable to a future SoS context. The problem is in part addressed in an emerging SoS framework in the manufacturing domain called Industry 4.0. It focuses on connected and digitalized production with the ambition of increasing flexibility and efficiency. This paper investigates how Industry 4.0 standards can be used in an SoS context to make CS more flexible and adaptive, and evaluates their usefulness outside manufacturing. The study is based on a case from the construction domain, for which a generic SoS architecture is developed. Several extensions and adaptations of Industry 4.0 are suggested, including specifications of ontologies for missions and workflows.